Persistent Inflammation and Nitric Oxide Dysregulation Are Transcriptomic Blueprints of Subglottic Stenosis - Nguyen, Hoang C. B.; Chao, Tiffany N.; Cohen, Noam A.; Mirza, Natasha (Frontiers in Immunology, 2021)
Subglottic stenosis (SGS) is a recurrent, obstructive, fibroinflammatory disease of the upper airway resulting in severe dyspnea, dysphonia, as well as other potentially fatal complications. Although aberrant inflammation and wound-healing are commonly associated with pathogenesis, the mechanism through which such processes occur and recur in affected patients remains poorly studied. Here we report that transcriptomic profiling of laryngotracheal regions from minimally-invasive mucosal swabs of SGS patients reveals a distinctively pro-inflammatory gene signature. Surprisingly, comparative genomics between SGS patients and mice with direct laryngotracheal injury suggest that SGS patients bear more resemblance to the acute than chronic phase of injury. Furthermore, functional and regulatory network analyses identify neutrophilic involvement through hyper-activation of NF-κB and its downstream inflammasome as a potential master regulator. Interestingly, nitric oxide synthesis was found to be downregulated in SGS patients compared to healthy controls. Thus, SGS represents a state of immunodeficiency whereby defective immune clearance triggers recurrent, long-lasting production of pro-inflammatory cytokines.